2019
DOI: 10.21273/hortsci14131-19
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Rutin and Protodioscin in Different Tissue Parts of Asparagus (Asparagus officinalis L.)

Abstract: Asparagus is a popular vegetable rich in healthy functional components. Asparagus spears are known to contain a large amount of rutin, which has been found to possess anti-inflammatory, antitumor, and antibacterial/viral properties, and protodioscin, which is an antitumor substance and present in the bottom parts (8 cm from the cut end). However, the process of its production leaves fern in the aboveground parts and roots in the underground parts as significant amounts of nonusable parts, and this issu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 25 publications
(50 reference statements)
5
8
0
Order By: Relevance
“…However, spears that have not been harvested at the optimum time also contain a large amount of rutin and may be useful components or resources of rutin (Motoki et al, 2012a). In addition, although a significant amount of rutin was detected in the aboveground parts, which is consistent with the results of previous studies (Motoki et al, 2012b), it was also found in the storage roots (Motoki et al, 2019). The largest amount of protodioscin was found in the buds as well as in young fruit and seeds among the aboveground parts (Motoki et al, 2019).…”
supporting
confidence: 89%
See 4 more Smart Citations
“…However, spears that have not been harvested at the optimum time also contain a large amount of rutin and may be useful components or resources of rutin (Motoki et al, 2012a). In addition, although a significant amount of rutin was detected in the aboveground parts, which is consistent with the results of previous studies (Motoki et al, 2012b), it was also found in the storage roots (Motoki et al, 2019). The largest amount of protodioscin was found in the buds as well as in young fruit and seeds among the aboveground parts (Motoki et al, 2019).…”
supporting
confidence: 89%
“…In addition, although a significant amount of rutin was detected in the aboveground parts, which is consistent with the results of previous studies (Motoki et al, 2012b), it was also found in the storage roots (Motoki et al, 2019). The largest amount of protodioscin was found in the buds as well as in young fruit and seeds among the aboveground parts (Motoki et al, 2019). However, the influences of the cultivation method and environmental conditions on the levels of rutin and protodioscin have not been clarified.…”
supporting
confidence: 82%
See 3 more Smart Citations